Production of Cocoa Kombucha from Cocoa Bean Husk and Cocoa Juice - Chungsiriporn, Juntima; Chairerk, Nirana; Pongyeela, Prukraya; Prajongphongphan, Jetniphat; Kaewmanee, Nontapun (Journal of Science and Technology CRRU, 2025)
This research studies the optimal conditions for producing cocoa kombucha beverage from cocoa bean husks and fresh cocoa juice. Study on the effects of cocoa bean husk tea concentration at 4-10% (w/v), initial total soluble solids at of 15-30 oBrix and concentrate volume at 10-40 mL. Changes in pH and total soluble solids during the fermentation process were measured, and antioxidant content was analyzed. The storage conditions of the cocoa kombucha beverage were also investigated. The results indicated that the most suitable conditions for producing cocoa kombucha with the highest antioxidant activity were a fresh cocoa tea concentration of 10% (w/v), an initial total soluble solid of 15 oBrix, and a concentrate volume of 10 mL. After 7 days of fermentation, the pH value was 3.05 and antioxidant activity reached 55.55%. When the cocoa kombucha was diluted with water at a ratio of 1:0.5 and the total soluble solids were adjusted to 15 °Brix, the most favorable taste was achieved. Storage at 4 °C resulted in increased fizziness and extended the beverage's shelf life to 14 days.